Does multisensory stimulation with virtual reality (VR) and smell improve learning? An educational experience in recall and creativity - Andonova, Veneta; Reinoso-Carvalho, Felipe; Jimenez Ramirez, Manuel Arturo; Carrasquilla, David (Frontiers in Psychology, 2023)
Purpose The purpose of this paper is to derive into practical recommendations from multisensory stimulation with virtual reality (VR) and scent to help educators develop effective teaching strategies geared toward aspects of the learning experience, recall, and creativity in a stereotypical learning context. Design/methodology/approach The paper is based on a randomized experiment in which student participants were subdivided into three treatment groups and one control group. Each group was stimulated by a different combination of visual, auditory, and olfactory stimuli (2D SMELL, VR, and VR SMELL) and the outcomes were compared against those of the control group (2D). Consistent with the Cognitive Theory of Multimedia Learning, hypotheses were constructed to study the effect of different combinations of stimuli on the learning experience and learning outcomes related to recall and creativity in a stereotypical learning context. Findings Traditional video content alone and bundled with a coherent olfactory stimulus prompted higher self-reported ratings of perceived quality of the sensory experience. Olfactory stimulus in combination with either VR or a traditional video prompted higher self-reported ratings on perceived immersion. In a stereotypical learning context, the highest recall scores were achieved with traditional video alone. Both VR alone and bundled with an olfactory stimulus resulted in enhanced creativity. Research limitations/implications The findings of this study should be interpreted in the context of adopting multisensory stimulations combined with VR technology as part of stereotypical learning contexts. Most professional educators do not have robust knowledge or experience in using build-on-purpose multisensory stimuli but are increasingly engaged in using multisensory tools such as VR, as part of their teaching practice. In relation to recall, the results are consistent with the hypothesis that in a stereotypical learning context, a multisensory experience involving VR and olfactory stimuli can be related to an undesired cognitive load for learners. There exists a possibility that the low-technical version of the VR goggles used, as well as the contents of the instructional video may have influenced the learning outcomes in terms of recall. Hence, future research should consider such aspects and focus on richer learning contexts. Originality/value This work offers practical recommendations for instructional design strategies aiming to create multisensory stimulations with VR and olfactory components to foster a richer learning experience and enhanced learning outcomes, under the assumptions of a stereotypical learning context.